Engaging patients to develop a customized digital health companion for periodontitis: Study protocol - Weinert, Lina; Listl, Stefan; Dannewitz, Bettina; Heinze, Oliver; Mostovic, Tanja; Kalmus, Olivier; El Sayed, Nihad (Frontiers in Oral Health, 2022)
Periodontitis is a chronic inflammatory disease resulting in the destruction of tooth-supporting tissues. It affects billions of people around the globe and substantiates an enormous economic burden to society. Digital tools such as mobile Health (mHealth) applications have the potential to increase patient engagement, knowledge about the disease, and adherence to treatment recommendations. Digital health companions represent a new kind of digital tool aiming to support patients throughout their course of periodontal care. This paper presents the study protocol of the Paro-ComPas project which aims to co-develop and evaluate a digital patient companion application (“app”) to empower patients along their journey with periodontitis. As a first step, a qualitative study design encompassing semi-structured interviews with patients and experts as well as focus group discussions (FGD) will be used. Patients in different stages of periodontal care will be recruited from dental practices across Germany and are invited to share their experiences and opinions about their care and potential areas for support. Experts from relevant areas (e.g., mHealth, behavior change psychology, oral health, and dental hygiene) will be interviewed to map a holistic view on the current delivery of care and best practices of mHealth development. After setting up a minimal viable product (MVP) based on a requirements analysis, FGDs with patients will take place to incorporate user feedback and finalize the development of the prototypic app. The prototypic app will then be evaluated in a randomized, multi-center clinical trial in comparison with the current standard of care. Finally, a comprehensive implementation roadmap will be developed together with all relevant stakeholders. This comprehensive approach will allow us to map the patient journey and develop a digital health companion tailored to the needs of patients with periodontitis using an already existing indication independent medical companion toolbox. Novel insights into patients’ knowledge and perception of periodontal disease as well as barriers in adherence to periodontal care pathways will be provided. This knowledge will be converted in a systematically tailored companion app to serve the needs and preferences of people to better address periodontitis. The results from the clinical trial will provide unique insights into the extent to which the patient companion app contributes to adherence to periodontal care. Although mHealth applications have become popular in recent years, only few apps focusing on promotion of oral health have been released so far. Our study presents a novel and comprehensive approach to both co-developing and evaluating a proof of concept for a digital health companion for patients with periodontitis.